Pengaruh Penempatan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pegawai Kantor Dinas PUPR Kabupaten Tanah Datar - Habil Dwi Putra; Zefriyenni Zefriyenni; Nila Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Performance at the PUPR District Office Tanah Datar has not reached the target for 4 years. This study aims to examine the Effect of Placement and Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable using secondary data obtained by distributing questionnaires to 50r6 permanent employees who are used as respondents at the PUPR DINAS Office of Tanah Datar Regency. In this study using the analysis tool Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of this study indicate that (1) Placement has a positive and significant effect (0.000 <0.05) on job satisfaction. (2) Work environment has a positive and significant effect (0.000 <0.05) on job satisfaction. (3) Placement has a positive and significant effect (0.027 > 0.05) on Employee Performance. (4) Work Environment has no effect (0.237 <0.05) on Employee Performance. (5) Job satisfaction has a positive and significant effect (0.004 <0.05) on employee performance. (6) Placement has an effect and significant (0.035 <0.05) on Employee Performance through Job Satisfaction. (7) Work Environment has a positive and significant effect (0.012 <0.05) on Employee Performance through Job Satisfaction. (8) The contribution of placement and work environment variables to employee performance is 0.865 or 86.5% and the remaining 13.5% is influenced by other variables not examined in this study. (9) The contribution of placement, work environment and job satisfaction variables to employee performance is 0.871 or 87.1% and the remaining 12.9% is influenced by other variables not examined by this study.